The Influence of Corporate Social Responsibility on Company Value with Profitability as a Oderation Variable in Registered Manufacturing Companies on the Indonesian Stock Exchange Period 2019-2021 - Melliana, Saur; Butarbutar, Hotlan; Siahaan, Dinda G.J (Indonesian Journal of Banking and Financial Technology, 2024)
This research aims to determine the influence of CSR (Corporate Social Responsibility) on company value in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample used in this research was purposive sampling, totaling 56 companies with 3 years of observation and obtained from the annual financial reports of manufacturing and component companies at www.idx.co.id. The data analysis used is SPSS version 25 analysis. The results of the research show that CSR (Corporate Social Responsibility) has a significant positive effect on company value and profitability as proxied by ROA (Return On Assets) and moderates the relationship between CSR and Company Value.